The Association Between Self-Regulation and Daily Sports Activities in a Nationally Representative Sample of Older Adults. Findings From the German Ageing Survey - Hajek, André; König, Hans-Helmut (Frontiers in Physiology, 2018)
There is a large body of literature about the determinants of exercising regularly in older adults. However, to date, there is limited evidence showing that self-regulation is associated with exercising regularly. Existing studies are mostly restricted to rather specific or small samples. Thus, the purpose of this study was to examine whether self-regulation is associated with daily sports activities among older adults. For the current study, cross-sectional data were used from the German Ageing Survey (n=7,757), a nationally representative sample of community-dwelling individuals aged 40 and over in Germany. Logistic regression analysis showed that daily sports activities is positively associated with self-regulation [OR: 1.32 (95%-CI: 1.11-1.58)]. The present study highlights the importance of an association between daily sports activities and self-regulation. Knowledge about this association is useful in addressing cases where older adults exercise l.ess than daily.